The Human Security Implications of Migration on Zimbabwean Migrant Women in South Africa - Mutambara, Victoria; Maheshvari, Naidu (African Human Mobility Review, 2021)
A large number of people enter the South African borders legally and illegallyfrom Zimbabwe in pursuit of secure, better living conditions. Amongst thosepeople are women. This paper argues that most of the women who migrate toSouth Africa escape from insecurity in Zimbabwe, only to be confronted withother human security challenges in South Africa. The paper presents an overviewof the theoretical framework of the human security paradigm, which helps tounpack how the experiences of Zimbabwean migrant women can be labelled asforms of insecurity. Using qualitative data, the paper discusses the possiblehuman insecurity aspects that force the women to leave their home country andthe challenges that they encounter in the host country. The findings of the paperindicate that economic insecurity and poverty highly influence the decisions andchoices for migration for most of the women. However, the women’s expectationsof better lives and human security appear to contradict their social experiences.The migrant women face multiple forms of discrimination and violence that areconstructed around their identities as women, non-citizens and black Africans.Cumulatively, most of the women experience gender-based violence anddiscrimination from South African citizens, foregrounded in xenophobicsentiments. Therefore, this paper reaches the conclusion that migrant womenare victims of the compounded trauma of insecurities, as many of them wouldhave encountered human insecurity consequences in their home country.